2020
DOI: 10.1093/toxres/tfaa009
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera leaves extract modulates toxicity, sperms alterations, oxidative stress, and testicular damage induced by tramadol in male rats

Abstract: Tramadol is a synthetic opioid analgesic used for moderate-to-severe pain structurally related to codeine and morphine, where their analgesic mechanism is a result of opioid and non-opioid mechanisms. This study was designed to evaluate the effects of Moringa oleifera leaves extract (MLE) on tramadol-induced testicular toxicity, sperm changes, testicular damage, and oxidative stress in male rats. Forty male albino rats were divided into four groups and treated for 4 weeks (group 1, as control; group 2, MLE; gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
7
9
0
1
Order By: Relevance
“…Administration of MOLE in obesity-induced groups improved these parameters to similar levels as the control and MOLE groups. Our findings agree with previous studies, which reported that the administration of MOLE ameliorates tramadol-induced (Abd et al, 2020) or melamine-induced (Mansour et al, 2020) testicular injuries by abolishing oxidative stress and improving the seminal parameters in male rats.…”
Section: Discussionsupporting
confidence: 93%
“…Administration of MOLE in obesity-induced groups improved these parameters to similar levels as the control and MOLE groups. Our findings agree with previous studies, which reported that the administration of MOLE ameliorates tramadol-induced (Abd et al, 2020) or melamine-induced (Mansour et al, 2020) testicular injuries by abolishing oxidative stress and improving the seminal parameters in male rats.…”
Section: Discussionsupporting
confidence: 93%
“…Testosterone and oxidative stress reportedly improved in i n vitro models of Leydig cells treated with different antioxidant compounds [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Similar results were observed across various animal models of induced hypogonadism by using vitamins A and C [ 171 ], zinc [ 172 ], N -acetylcysteine (NAC) [ 173 , 174 ], gallic acid [ 175 ], lycopene [ 176 ], forskolin [ 177 ], resveratrol [ 167 , 178 ], Nigella sativa seed oil [ 179 ], Lycium chinense Mill [ 180 ], Eruca sativa seeds [ 181 ], Moringa oleifera leaves [ 182 ], Schisandra chinensis [ 183 ], Ojayeonjonghwan [ 184 , 185 ], and Qilin pills [ 186 ] ( Supplementary Table S2 ).…”
Section: Management Of Male Hypogonadism Associated With Non-communicable Chronic Diseasessupporting
confidence: 55%
“…Therefore, it is important for plants to be evaluated for their toxicity to know how safe they are for human use. Accumulative research shows that Moringa oleifera exhibits a lot of important biological properties such as antioxidant, anti-inflammation, anti-hyperglycemic properties over the past years proving that it is a good plant to use as an alternative therapeutic for diabetes ( Omodanisi et al, 2017b ; Gothai et al, 2017 ; Paula et al, 2017 ; Abd et al, 2020 ; Xiong et al, 2021 ). In vitro and in vivo studies that have been conducted to show that this plant has no lethal dose and is safe to use.…”
Section: Safety and The Toxicity Profile Of Moringa Oleiferamentioning
confidence: 99%